Two antiviral proteins from tobacco: purification and characterization by monoclonal antibodies to human beta-interferon. - Edelbaum, O (1990)
Polyclonal antibodies to human beta-interferon reacted specifically with two plant proteins (gp22 and gp35) by Western blot analysis of crude protein extracts from tobacco leaves infected with tobacco mosaic virus. Immunoaffinity chromatography of these extracts on a column of immobilized monoclonal antibodies to human beta-interferon and then reversed-phase HPLC yielded gp22 and gp35 in a pure state. Both proteins reacted with the Schiff reagent and concanavalin A (indicating their glycoprotein nature) and exhibited antiviral activity (inhibiting tobacco mosaic virus replication in tobacco-leaf discs at concentrations of ng/ml). Each protein was cleaved by cyanogen bromide and the resultant peptides, separated by HPLC, were sequenced as far as the Edman degradation allowed, giving a total of 61 amino acid residues for gp22 and 105 residues for gp35, which represent 30-50% of their expected length. Computer analyses of the sequenced segments revealed no significant homology to human beta-interferon, each other, or any other recorded sequence.